Before we say goodbye - Kawaguchi, Toshikazu, 1971-; Trousselot, Geoffrey (London : Picador, 2023)
The regulars at the magical Cǎf Funiculi Funicula are well acquainted with its famous legend and extraordinary time-travel offer. Many patrons have reunited with old flames, made amends with estranged family and visited loved ones. But the journey is not without risks, and there are rules to follow. In the tradition of Toshikazu Kawaguchi's sensational Before the Coffee Gets Cold Series, readers will once again be introduced to a new set of visitors: the husband with something important left to say; the woman who couldn't bid her dog farewell; the woman who couldn't answer a proposal; and the daughter who drove her father away.
I. The husband -- II. The farewell -- III. The proposal -- IV. The daughter.
Originally published as: Sayonara mo ienai uchi ni. Tokyo : Sunmark Publishing, Inc., 2021.
First published.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School
Translated from the Japanese.
Keywords: Time travel -- Fiction; Coffeehouses -- Japan -- Fiction; Life change events -- Fiction; Interpersonal relations -- Fiction; Japanese fiction